Study on the Aging Time Variation Law of Mechanical Properties of the Laminated Rubber Bearing in Coastal Bridges considering Frictional Slip - Yue Li; Chongming Gao; Chong Li; Qian Li (Shock and Vibration)
As an important support member in the structural system of coastal bridges, the frictional slip and the rubber aging of laminated rubber bearings will affect the service safety of the overall structure in earthquakes. In order to investigate the mechanical properties aging law of the rubber bearings considering frictional slip in the coastal bridges, a frictional slip experiment was carried out on the laminated rubber bearings. Moreover, the influence of rubber aging on the mechanical properties of the bearings with various shape coefficients was analyzed by the finite element method during the 100 years of service life of bridges. The results indicate that (1) the horizontal and vertical stiffness of the bearing increase linearly with the aging time of the rubber. The amplification of the bearing stiffness also grows with the shape coefficient of the bearing. (2) The frictional slip initiation displacement of the bearing grows with the rubber aging time. Furthermore, the larger the shape coefficient of the bearing is, the more the frictional slip initiation displacement of the bearing increases. (3) With the increase of the aging time, the equivalent viscous damping ratio of the bearing continues to increase and more energy is consumed by frictional slip. For the bearing with the shape coefficient of 16.38, the equivalent viscous damping ratio at 100 years of rubber aging time is 1.17 times higher than that of the initial state of the bearing, and 33.21% more energy is consumed through frictional slip. Given that the marine environment accelerates rubber aging and changes the mechanical properties, the effects of the frictional slip and rubber aging properties of the laminated rubber bearings on the seismic dynamic response of bridges should be considered in the seismic design of coastal bridges.